2023
DOI: 10.3389/fphar.2023.1110460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of polymorphisms in CYP and UGT enzymes and ABC and SLCO1B1 transporters on the pharmacokinetics and safety of desvenlafaxine

Abstract: Venlafaxine pharmacokinetic variability and pharmacotherapy outcomes are well known to be related to CYP2D6 pharmacogenetic phenotype. In contrast, scarce pharmacogenetic information is available nowadays concerning desvenlafaxine, its active metabolite first marketed in 2012. The aim of this study was to evaluate the impact of 29 alleles in 12 candidate genes (e.g., CYP enzymes like CYP2D6, CYP3A4, or CYP2C19; ABC transporters like ABCB1; SLCO1B1; and UGT enzymes like UGT1A1) on desvenlafaxine pharmacokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
3
3
0
Order By: Relevance
“…Desvenlafaxine pharmacokinetic parameters were consistent with the information available in the literature [ 14 ] and our previous work [ 13 ], where linear pharmacokinetics was observed. Here, healthy female volunteers presented a higher C max /DW; this association was also described in our previous work with the same clinical trials but fewer volunteers [ 13 ] and may be explained by sex-specific physiological differences in drug absorption [ 19 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Desvenlafaxine pharmacokinetic parameters were consistent with the information available in the literature [ 14 ] and our previous work [ 13 ], where linear pharmacokinetics was observed. Here, healthy female volunteers presented a higher C max /DW; this association was also described in our previous work with the same clinical trials but fewer volunteers [ 13 ] and may be explained by sex-specific physiological differences in drug absorption [ 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…Desvenlafaxine pharmacokinetic parameters were consistent with the information available in the literature [ 14 ] and our previous work [ 13 ], where linear pharmacokinetics was observed. Here, healthy female volunteers presented a higher C max /DW; this association was also described in our previous work with the same clinical trials but fewer volunteers [ 13 ] and may be explained by sex-specific physiological differences in drug absorption [ 19 ]. Fed healthy volunteers showed a higher AUC ∞ /DW and C max /DW compared to fasting healthy volunteers; this effect in C max is well described in previous studies [ 20 ], including ours [ 13 ], where only a tendency was observed for AUC ∞ /DW, consistent with the present study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Blood levels of some ADs are known to be reduced in smokers due to induction of metabolism mediated by the enzymes CYP1A2 and CYP2B6 [153]. Note: * Also metabolized by conjugation mediated by isoforms of UGT (UGT1A9, UGT2B15) [202] ** Metabolized predominantly by conjugation mediated by isoforms of UGT (UGT1A1, UGT1A3, UGT2B4, UGT2B15 и UGT2B17) [195] It is unrealistic to expect that practicing psychiatrists have the desire and ability to regularly study the scientific literature in addition to their clinical work. This partly explains why it is necessary to translate reliable scientific evidence into informative clinical recommendations regarding the use of PGx to assess the risk of AD-induced QTc prolongation.…”
Section: The Role Of Pharmacogenetics and Pharmacokinetics Of Antidep...mentioning
confidence: 99%